2021
DOI: 10.1177/23094990211017355
|View full text |Cite
|
Sign up to set email alerts
|

Open-wedge high tibial osteotomy in patients with discoid lateral meniscus

Abstract: Background: There are concerns about the progression of the lateral osteoarthritis (OA) should be taken into account when high tibial osteotomy (HTO) is performed in patients with discoid lateral meniscus (LM). This study evaluated the clinical results of HTO in patients with discoid LM and elucidated factors affecting the results. Methods: This study evaluated 32 female patients with varus deformity and medial OA. Patients with discoid LM (8 patients) or without discoid LM (24 patients) underwent open-wedge H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Pathology of the lateral meniscus is not an absolute contraindication to a valgus-producing HTO. Multiple studies have demonstrated that patients with discoid lateral menisci experience improvements in pain and patient-reported outcomes (PROs) after valgus-producing HTOs 54,55 . However, they are at risk for meniscal tear progression and radiographic progression of lateral joint-space narrowing, which may, in some cases, lead to increased pain, and they should be informed of these risks 55,56 .…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Pathology of the lateral meniscus is not an absolute contraindication to a valgus-producing HTO. Multiple studies have demonstrated that patients with discoid lateral menisci experience improvements in pain and patient-reported outcomes (PROs) after valgus-producing HTOs 54,55 . However, they are at risk for meniscal tear progression and radiographic progression of lateral joint-space narrowing, which may, in some cases, lead to increased pain, and they should be informed of these risks 55,56 .…”
Section: Indications and Contraindicationsmentioning
confidence: 99%